Analisis dan Perancangan Sistem Informasi Pengiriman Surat Berbasis Web pada Perusahaan Ekspedisi PT. Djakarta Ekspress - Mira Permatasari; Ahmad Taufik (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2026)
PT. Djakarta Ekspress is an expedition company that still uses a manual system for its mail delivery operations, leading to various problems such as delayed data input, difficulties in archive searches, vulnerability to data loss, and the absence of real-time delivery tracking features. This research aims to analyze the existing manual system, design, and implement a web-based mail delivery information system as a solution to improve the company’s operational efficiency and effectiveness. The development method used is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and evaluation. The implementation results show that the web-based system enables faster and more accurate mail data recording, automatic courier assignment, and safer data storage in a database. The system is also equipped with real-time delivery tracking features and the ability for couriers to upload delivery proof in the form of photos, thus assisting both admin and customers in monitoring delivery status. System evaluation based on questionnaire data shows a significant improvement from the "Very Poor" to "Very Good" category in terms of ease of use, feature completeness, and user satisfaction. Additionally, strengthening data security with encryption, two-factor authentication, and system scalability testing is recommended for future development. This system has proven to be effective in enhancing the efficiency, professionalism, and competitiveness of PT. Djakarta Ekspress in the digital era.